FACTORS SPECIFIC TO THE PROCESS OF FORMING THE PSYCHOLOGY OF SCHOOL STUDENTS - Dustkobilov Rustam Dusmamat ugli (Euro Asian Journal Publishing, 2025)
The importance of psychology in organizing the educational process taking into account the age, psychological and individual characteristics of the student, improving the psychological state of the student and coordinating his attitude to the lesson is highly appreciated. This article describes the individual psychological characteristics of schoolchildren
Keywords: exopsychic; endopsychic; character